Effects of credit constraints on rural household technical efficiency: Evidence from a city in northern China. Issue 4 (28th October 2014) - Zhao, Jianmei; J. Barry, Peter
Abstract : Purpose: – The purpose of this paper is to evaluate the effects of access to formal credit on rural household technical efficiency in China. Design/methodology/approach: – Based on the rural household survey data in Weifang city, Shandong province in northern China, the authors apply recent developed bootstrapped DEA approach to investigate rural technical efficiency at the household level under the consideration of off-farm activities. Rural households are then identified as credit constrained and classified as supply-side and demand-side credit constraints by applying direct elicitation method. Finally, the authors apply a tobit regression to examine the effects of credit constraints on household technical efficiency. Findings: – Rural households in China not only suffer supply-side credit constraints, but also demand-side credit constraints resulted from the transaction costs and risk rationing. The tobit regression discloses that demand-side credit constraints impose significant negative impacts on household technical efficiency. Originality/value: – The authors clarify the definition of credit constraints and classify the credit constraints into supply-side and demand-side credit constraints. The results of this paper have significant policy implications for rural finance policies in China.